Efficacy of esomeprazole at treatment of patients with gastroesophageal reflux disease - Yu. V. Yevsyutina (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of review. To present literature data on efficacy and safety of esomeprazole for the treatment of gastroesophageal reflux disease (GERD). Summary. GERD is one of the most widespread chronic diseases. Proton pump inhibitors (PPI) are the basic treatment of GERD that promote symptom relief (both esophageal, and extraesophageal) as well as the healing of esophageal mucosa lesions, prevent development of relapses and complications of reflux esophagitis. Results of multiple studies prove that esomeprazole is a highly effective antisecretory drug which can be used as for treatment of patients with erosive esophagitis and non-erosive reflux disease and as a maintenance therapy. Conclusion. Esomeprazole, in particular generic drug Emanera, is one of the most effective and safe antisecretory drugs. Pharmacokinetic and pharmacodynamic properties of the drug determined its ability to relief heartburn faster than other PPIs, to provide higher rate of erosion healing than omeprazole. In addition, esomeprazole (Emanera®) possess more pronounced antisecretory effect, than omeprazole that results in higher treatment compliance of the patients.